PENGARUH PEMBERIAN INSENTIF, KOMPETENSI DAN BEBAN KERJA TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. BANK TABUNGAN PENSIUN NASIONAL (BPTN) CABANG PEKANBARU - Arif Firdaus; Nuryanti '; Rovanita Rama (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose this study was to determine how influence of incentives, competence and expenses work to discipline employees at PT. National Pension Savings Bank (BPTN) Branch Pekanbaru. The population in this study are employees of the National Pension Savings Bank (BTPN) Branch Pekanbaru 2015 that amounted to 77 people. While the sampling technique using census method. Analysis of data using multiple linear regression with SPSS version 18:00. Based results of data analysis known that providing incentives, competencies and expenses work partially and simultaneously have influence to discipline of employees at PT. National Pension Savings Bank (BTPN) Branch Pekanbaru. The large number of such influence is 61.9%. Expected to companies in order to improve work discipline of its employees by providing attractive incentives, improving the competence of employees in the work and adjust the workload for employees. For example, by giving sanctions against employees who violate company rules and regulations so that it can make employees very alert and careful in work.Keyword : Incentives, Competence, Expenses Work and Discipline Employees.